Identifikasi bakteri di mangrove Desa Sawohan Sidoarjo sebagai agen bioremediasi dari pencemaran logam berat - Vella Rohmayani; Nurhidayatullah Romadhon; Holly Ichda; Anindita Riesti Retno Arimurti; Mohammad Taufiq Shidqi; Wiwi Wikanta (Poltekkes Kemenkes Aceh, 2024)
Background: Remediation of heavy metal pollutants using bacteria is currently being carried out due to high levels of heavy metal pollution (Cu and Hg) in ecosystems, mainly due to industrial growth, encouraging remediation research using bacteria. The toxic effects of heavy metals on living things and the environment need to be addressed.Objective: This study aims to identify and analyze the potential of indigenous bacteria from mangrove sediments in Sawohan Sidoarjo Village in reducing Cu and Hg heavy metal levels in vitro.Method: This research is included in explorative descriptive research. This research was conducted at the UMSurabaya microbiology laboratory, in July – November 2023. Isolation is carried out by pour plate method and purified using streak plate method on Nutrient Agar medium. Initial screening of bacteria using Nutrient Agar medium with the addition of Cu and Hg metals as much as 100, 250, 350 and 500 ppm. Measurement of the potential of bacteria in reducing Cu and Hg metal levels was carried out on SSA medium (Salmonella shigela agar) using the Langmuir method. The results of bacterial isolation from mangrove sediments obtained 9 isolates used to test the degradation ability of heavy metals Cu and Hg.Result: U Heavy metal degradation test showed that the 9 isolates were able to degrade Cu and Hg heavy metals. T1 isolates of Pseudomonas aeruginosa species, with Gram negative characteristics, have the highest reduction ability with Cu reduction power of 82% and Hg metal of 72,61%.Conclusion: H Pseudomonas aeruginosa bacteria from mangrove sediments has the ability as a bioremediation agent of heavy metals Cu and Hg from ecosystems.